Adapting english teaching to engage Malaysian male learners - Andrew N. Williams; Kavarljit Kaur Gill (2014)
While many female students are diligent in their studies, many male students do not seem to engage with the learning process. This situation cannot be blamed on the maleness of the students, we should find more effective ways to teach these students. There has been a substantial amount of research on male learning preferences and on the global phenomenon of female students outperforming male students. Drawing from this research we suggest practical approaches to teaching English to Malaysian male students that are likely to lead to better results.